Merchants and noble anxieties: integration and social mobility of the Malo de Molina family - Mogrovejo Vidal, David (2020)
This paper discusses the social and cultural dimensions of the merchant’s upward social mobility in the Viceroyalty of Perú during the 17th century from the case study of Melchor Malo de Molina’s elite integration. This Spanish merchant arrived in Perú in the late 16th century and, in a few decades, became a prominent member of Peruvian society’s most exclusive circuits. I propose that his bonding and control over other prestigious families’ patrimony and the construction of a public image of nobility were key in his success.